An explicit bound for the first sign change of the Fourier coefficients of a Siegel cusp form - Ch'oe, Yŏng-ju; Gun, Sanoli; Kohnen, Winfried (International mathematics research notices, 2014)
We give an explicit upper bound for the first sign change of the Fourier coefficients of an arbitrary nonzero Siegel cusp form F of even integral weight on the Siegel modular group of arbitrary genus g≥2.